A Qualitative Study of School Social Workers' Roles and Challenges in Dropout Prevention. Issue 2 (7th February 2018) - Webber, Kristina C
Abstract: High school dropout remains a persistent educational and social problem in the United States, despite promising declines in dropout rates. Social workers are uniquely positioned to identify and address numerous factors influencing students' likelihood of graduating. The purpose of this small qualitative study was to describe social workers' engagement in dropout prevention efforts and the context in which this work occurs. Through interviews with school social workers, school counselors, and district-level administrators, three focal practice areas were identified: (1) supporting student attendance, (2) providing intensive support for selected at-risk students, and (3) encouraging dropouts to return to a diploma-granting program. Respondents also identified common barriers and ethical dilemmas that hindered their practice, including challenges in defining the scope and boundaries of the social work profession, and tensions between the needs of the school and the needs of students. Suggestions for future research are provided, and implications for policy, practice, and the education of future school social work practitioners are discussed.